Semaphorin4D Induces Inhibitory Synapse Formation by Rapid Stabilization of Presynaptic Boutons via MET Coactivation - Frias, Cátia P. (J Neurosci, 2019)
Changes in inhibitory connections are essential for experience-dependent circuit adaptations. Defects in inhibitory synapses are linked to neurodevelopmental disorders, but the molecular processes underlying inhibitory synapse formation are not well understood. Here we use high-resolution two-photon microscopy in organotypic hippocampal slices from GAD65-GFP mice of both sexes to examine the signaling pathways induced by the postsynaptic signaling molecule Semaphorin4D (Sema4D) during inhibitory synapse formation. By monitoring changes in individual GFP-labeled presynaptic boutons, we found that the primary action of Sema4D is to induce stabilization of presynaptic boutons within tens of minutes. Stabilized boutons rapidly recruited synaptic vesicles, followed by accumulation of postsynaptic gephyrin and were functional after 24 h, as determined by electrophysiology and immunohistochemistry. Inhibitory boutons are only sensitive to Sema4D at a specific stage during synapse formation and sensitivity to Sema4D is regulated by network activity. We further examined the intracellular signaling cascade triggered by Sema4D and found that bouton stabilization occurs through rapid remodeling of the actin cytoskeleton. This could be mimicked by the actin-depolymerizing drug latrunculin B or by reducing ROCK activity. We discovered that the intracellular signaling cascade requires activation of the receptor tyrosine kinase MET, which is a well known autism risk factor. By using a viral approach to reduce MET levels specifically in inhibitory neurons, we found that their axons are no longer sensitive to Sema4D signaling. Together, our data yield important insights into the molecular pathway underlying activity-dependent Sema4D-induced synapse formation and reveal a novel role for presynaptic MET at inhibitory synapses. SIGNIFICANCE STATEMENT GABAergic synapses provide the main inhibitory control of neuronal activity in the brain. We wanted to unravel the sequence of molecular events that take place when formation of inhibitory synapses is triggered by a specific signaling molecule, Sema4D. We find that this signaling pathway depends on network activity and involves specific remodeling of the intracellular actin cytoskeleton. We also reveal a previously unknown role for MET at inhibitory synapses. Our study provides novel insights into the dynamic process of inhibitory synapse formation. As defects in GABAergic synapses have been implied in many brain disorders, and mutations in MET are strong risk factors for autism, our findings urge for a further investigation of the role of MET at inhibitory synapses.